2021
DOI: 10.3389/fpsyt.2021.733998
|View full text |Cite
|
Sign up to set email alerts
|

REM Sleep Fragmentation in Patients With Short-Term Insomnia Is Associated With Higher BDI Scores

Abstract: Objective: To observe the changes in sleep characteristics and BDI scores in patients with short-term insomnia disorder (SID) using a longitudinal observational study.Methods: Fifty-four patients who met the criteria for SID of the International Classification of Sleep Disorders, third edition, were recruited. Depression levels were assessed using the Beck depression inventory (BDI) at enrollment and after 3 months of follow-up, respectively. Sleep characteristics were assessed by polysomnography.Results: Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Then, using linear regression, they generated a regression model that could predict the risk of endogenous depression with 83.7% accuracy. These findings, together with other pioneering work, support the use of REM sleep behavior as a viable endogenous depression predictor marker, indicating that REM-D could also predict the therapeutic outcome [ 119 , 124 ].…”
Section: Rem Sleep Deprivation As a Non-pharmaceutical Choice For Tre...supporting
confidence: 67%
See 1 more Smart Citation
“…Then, using linear regression, they generated a regression model that could predict the risk of endogenous depression with 83.7% accuracy. These findings, together with other pioneering work, support the use of REM sleep behavior as a viable endogenous depression predictor marker, indicating that REM-D could also predict the therapeutic outcome [ 119 , 124 ].…”
Section: Rem Sleep Deprivation As a Non-pharmaceutical Choice For Tre...supporting
confidence: 67%
“…Besides its antidepressant efficacy, REM sleep fragmentation was closely associated with depressive status after a study conducted on 54 depressed patients with short-term insomnia disorder. Wu et al developed a REM sleep fragmentation-based regression model that could predict the risk of endogenous depression with an 83.7% prediction accuracy, thus promoting REM as a viable index for estimating depression risk and a biomarker for treatment response [ 119 ].…”
Section: Rem Sleep Deprivation As a Non-pharmaceutical Choice For Tre...mentioning
confidence: 99%
“… 1 2 A study found that fragmented rapid eye movement (REM) sleep in individuals with insomnia is associated with higher Beck Depression Inventory (BDI) scores. 3 REM sleep architecture disruption is a typical symptom of insomnia. 4 Sleep homeostasis and plasticity interact with each other and jointly regulate sleep patterns and sleep quality.…”
mentioning
confidence: 99%